The MicroRNA-Based Strategies to Combat Cancer Chemoresistance via Regulating Autophagy - Lei, Yuhe; Chen, Lei; Liu, Junshan; Zhong, Yinqin; Deng, Lijuan (Frontiers in Oncology, 2022)
Chemoresistance frequently occurs in cancer treatment, which results in chemotherapy failure and is one of the most leading causes of cancer-related death worldwide. Understanding the mechanism of chemoresistance and exploring strategies to overcome chemoresistance have become an urgent need. Autophagy is a highly conserved self-degraded process in cells. The dual roles of autophagy (pro-death or pro-survival) have been implicated in cancers and chemotherapy. MicroRNA (miRNA) is a class of small non-coding molecules that regulate autophagy at the post-transcriptional level in cancer cells. The association between miRNAs and autophagy in cancer chemoresistance has been emphasized. In this review, we focus on the dual roles of miRNA-mediated autophagy in facilitating or combating chemoresistance, aiming to shed lights on the potential role of miRNAs as targets to overcome chemoresistance.